Expression and Significance of Hypoxia‐Inducible Factor–1α and Survivin in Laryngeal Carcinoma Tissue and Cells. Issue 1 (19th October 2012) - Li, Da‐wei; Zhou, Liang; Jin, Bin; Xie, Jin; Dong, Pin
Abstract : Objective: The aim was to evaluate hypoxia‐inducible factor–1α (HIF‐1α) and survivin expression in laryngeal squamous cell carcinoma (LSCC) tissues and cell lines and to investigate whether HIF‐1α has an effect on the regulation of survivin gene expression in LSCC cells under hypoxia. Study Design: Prospective, observational. Setting: Shanghai Jiaotong University Affiliated First People's Hospital. Subjects and Methods: The expression of HIF‐1α and survivin protein in human LSCC tissues was analyzed by immunohistochemistry. HIF‐1α and survivin gene expression levels in Hep‐2 cells were detected by real‐time quantitative reverse transcription polymerase chain reaction (RT‐PCR) and Western blot under normoxic or hypoxic conditions. In hypoxic cells, HIF‐1α expression was inhibited by RNA interference. Results: HIF‐1α and survivin were both highly expressed in LSCC tissues and significantly related to the clinical stage and lymph node metastasis ( P <. 05). Meanwhile, a positive correlation existed between HIF‐1α and survivin expression ( r = 0.456, P <. 01). In LSCC cells, HIF‐1α and survivin expression were obviously upregulated in response to hypoxia ( P <. 05). The downregulation of HIF‐1α expression dramatically decreased survivin gene expression in hypoxic cells ( P <. 05). Conclusion: HIF‐1α could be considered as an important regulator for the upregulation of survivin gene expression induced by hypoxia in LSCC cells, and both proteins could be regarded as 2 key predictors of malignant progression and metastasis of LSCC.